Accessibility, equity and the sharing of water resources - Rémi Schweizer (Revue de Géographie Alpine)
While the supply of water to dry or arid mountain regions has long been a major challenge, the on-going processes of climatic and socio-economic change currently affecting the hydrosystems of the Alps raise the spectre of renewed pressure on water resources and possible local shortages. In such a context, questions relating to fair distribution of water are all the more sensitive given the tendency to neglect the social dimension of sustainability. The present paper makes both a conceptual and empirical contribution to this debate by analysing a system of distribution that has a long experience of water scarcity management: the community governance models traditionally linked to the irrigation channels, or bisses, typical of the Swiss Alpine canton of Valais. More specifically, we evaluate these models in terms of accessibility and equity, characteristics that we use to operationalize the notion of ‘fair distribution’. We examine these dimensions in three case studies with a view to highlighting the limitations of the aforementioned models. Indeed, despite their cooperative and endogenous nature, they tend to not only exclude certain members of the population, but also to reproduce rather than reduce social inequalities within the community. In general, these results challenge the rosy picture generally found in the literature relating to these community governance models.